Examination of the Operating Costs and Environmental Impact of Alternative Fuels Used in Ships - Tarik Kocal (Journal of Transportation and Logistics)
Nowadays, transportation has reached dimensions that have never been seen before, the amount of cargoes has diversified with quantity increases with the development of industry. Low cost, the number of goods transported, and security are the most important factors in the transportation sector. Due to these reasons, the majority of cargo transport in the world is carried out by seaway. In addition, the high increases in the costs of diesel fuel in ship transportation lead shipowners to use different fuels. Alternative fuels have started to be used on new ships and certain old ships. In this study in a one-year period, the costs and carbon dioxide emission values of alternative fuels that can be used in ships were calculated in different operating conditions. The ship used in this study has a diesel engine with a power of 5975 kW at full load. The costs of using LNG, LPG and methanol fuels as an alternative to diesel fuel (HFO, MDO) in the selected engine are calculated according to different load conditions and different annual working hours. When the results of the calculations are examined, it is seen which fuel could be more economical and environment friendly.